(Keynote) Wireless Wearable and Implantable Monitoring and Therapeutic Systems for Cardiac and Neurological Disorders. (23rd July 2018) - Ramasamy, Mouli; Varadan, Vijay
Abstract : Wearable nanosensor systems in the form of smart clothing, equipped with wireless communication technology, provides real-time medical data to health professionals for early diagnosis, planning therapeutic intervention, and following up on the effect of planned therapy. Techniques, such as electrocardiography (ECG), electroencephalography (EEG), electrooculography (EOG), electromyography (EMG) and electrical impedance tomography, are relevant to POC for cardiovascular disease, neurological disorders, cancer, and stroke. Intelligent wearable sensor systems with simple installation, minimal maintenance, and user involvement can be the best method for ubiquitous health monitoring. We have been working with a printable organic semiconductor and thin film transistor and have fabricated and tested various biosensors that can measure important physiological signs before and after surgery. Integrated into "smart" fabrics - garments with wireless technology – and independent e-bandaid sensors, nanosensors in tattoos and socks, minimally invasive implantable devices, the sensor systems will be able to monitor a patient's condition in real time and thus provide point-of-care diagnostics to health-care professionals and greater freedom for patients. This talk addresses this emerging area with selected videos of subjects for real time measurements and control cardiac and neurological diseases. Combined with state-of-the-art embedded wireless network devices to communicate with smartphone, laptop or directly to remote server through mobile network (GSM, 4G-LTE, GPRS), they can function as wearable wireless health-diagnostic systems that are more intuitive to use.